The Impact of System Quality and Inventory Control on Inventory Management Effectiveness through Operational Performance - Michael Austin Theos; Timotius FCW Sutrisno; Fahrul Riza (Journal of Economics and Management Scienties, 2026)
This study examines the influence of Perceived System Quality and Perceived Inventory Control Effectiveness on Inventory Management Effectiveness, with Perceived Operational Performance acting as a mediating variable. Grounded in the Resource-Based View (RBV), this research explores how technological resources and organizational capabilities contribute to operational outcomes within the inventory management activities of Wilmar Group Indonesia. A quantitative explanatory approach was employed using survey data collected from 80 respondents involved in warehouse and inventory operations. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. Indicator purification was also conducted to ensure construct validity and reliability. The findings indicate that Perceived Operational Performance is the strongest determinant of Inventory Management Effectiveness. Perceived System Quality has both direct and indirect effects on Inventory Management Effectiveness, indicating partial mediation through operational performance. Meanwhile, Perceived Inventory Control Effectiveness does not directly influence Inventory Management Effectiveness but significantly affects it indirectly through operational performance, indicating full mediation. These results highlight that operational performance serves as the primary mechanism through which organizational resources and capabilities generate effective inventory outcomes. The study contributes to the Resource-Based View by emphasizing that competitive advantage in inventory management depends not only on resource availability but also on the firm’s ability to operationalize those resources effectively. Practically, organizations should prioritize strengthening operational performance to maximize the benefits of system quality and inventory control practices.